Vibro-Acoustics, Volume 1 - Nilsson, Anders; Liu, Bilong (Springer Berlin Heidelberg : Imprint: Springer, 2015)
This three-volume book gives a thorough and comprehensive presentation of vibration and acoustic theories. Different from traditional textbooks which typically deal with some aspects of either acoustic or vibration problems, it is unique of this book to combine those two correlated subjects together. Moreover, it provides fundamental analysis and mathematical descriptions for several crucial phenomena of Vibro-Acoustics which are quite useful in noise reduction, including how structures are excited, energy flows from an excitation point to a sound radiating surface, and finally how a structure radiates noise to a surrounding fluid. Many measurement results included in the text make the reading interesting and informative. Problems/questions are listed at the end of each chapter and the solutions are provided. This will help the readers to understand the topics of Vibro-Acoustics more deeply. The book should be of interest to anyone interested in sound and vibration, vehicle acoustics, ship acoustics and interior aircraft noise. This is the first volume, and covers the following topics: Mechanical systems with one degree of freedom, Frequency domain, Waves in solids, Interaction between longitudinal and transverse waves, General wave equation, Wave attenuation due to losses and transmission across junctions, Longitudinal vibrations of finite beams, Flexural vibrations of finite beams, Flexural vibrations of finite plates. .